Participatory Communication and the Promotion of Sundanese Culture Through the Pakuwon Bantaragung Earth Market Event - Ridwan Firdaus; Dian Andriany (Green Publisher Indonesia, 2026)
The strengthening of globalization and the dominance of modern popular culture have contributed to the gradual fading of local cultural values, especially in rural areas that are rich in traditions. To respond to these challenges, community-based cultural events are used as an important strategy for cultural promotion and the development of sustainable tourism. This research aims to analyze the role of participatory communication in increasing tourism attraction and encouraging the advancement of Sundanese culture through the Pakuwon Earth Market event in Bantaragung Village, Majalengka Regency, focusing on its communication mechanisms, impacts, and strategies. This study uses a qualitative method, specifically a case study approach, in which data were collected through semi-structured interviews with three informants, participatory observation, and documentation studies, and analyzed using thematic analysis. The results indicate that dialogical, open, and inclusive participatory communication can increase awareness of Sundanese cultural values and strengthen community involvement by presenting meaningful tourism experiences. In addition, participation plays a role in transmitting cultural heritage values orally and strengthening a collective sense of belonging. This research concludes that participatory communication is an effective strategy for linking cultural advancement with the development of community-based cultural tourism and provides both theoretical and practical contributions to the development of sustainable tourism communication.